Systematic Literature Review: Students' Self-Regulated Learning at Different Levels of Education in Indonesia - Leana, Kunthy Ley; Saleh, Sitti Fithriani; Marup, M; Ilyas, Mutiara M. (Universitas Muhammadiyah Surakarta, 2024)
Self-regulated learning (SRL) is an important skill for students. Students who have SRL can regulate and control themselves in the learning process, especially when dealing with school assignments. The purpose of this study was to review the literature on students' SRL at different levels of education in Indonesia. This study is qualitative and uses the systematic literature review method. The data collection technique used in this study was a literature study and documentation sourced from articles using the keywords